Molecular phylogeny, morphology and taxonomy of Moroccan Triops granarius (Lucas, 1864) (Crustacea: Notostraca), with the description of two new species - Korn, Michael; Hundsdoerfer, Anna K. (Zootaxa, 2016)
We used three molecular markers to investigate populations of Triops granarius from a study area in western Morocco that had a north-south span of approx. 434 km, the most distant populations situated at more than 470 km distance from each other. Previous studies had already investigated two Triops granarius populations from this region and revealed their affiliation to the major phylogenetic lineage that includes Triops cancriformis. By contrast, based on the geographic position of the type locality and the morphology of the type, Triops granarius s.s. likely belongs to a clade that forms the sister group to American and Australian Triops, i.e. including Triops longicaudatus and Triops australiensis. In the present study a second, hitherto unknown phylogenetic lineage was discovered among Moroccan populations of Triops granarius s.l. Our phylogenetic analyses show that both Moroccan lineages of Triops granarius s.l. represent a pair of genetically and morphologically well differentiated sister species that should be separated from Triops granarius. We therefore formally describe them as two new species, Triops maximus sp. nov. and Triops multifidus sp. nov. The early larval stages of both species show a peculiar morphology with 10 to 15 setae on the exopodite of the 2nd antenna. The number of these setae was generally thought to span five to seven in Notostraca. Despite the fact that the antennal setae form a central part of the main locomotory organ in early instars, we found their number to vary by up to two between body-sides of single individuals.